RESEARCH INTO THE ACCURACY OF HOLES IN 3D PRINTING USING TAGUCHI METHOD (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article discusses the impact of two factors on the accuracy of the hole sizes - print speed and layer thickness in 3D printing. Nine samples of the ABS polymer were printed by using a 3D printer, then the impact of both of the factors on the accuracy of 3D printing of the holes was evaluated. Taguchi's method was applied with the help of DOE in Minitab to evaluate the impact of the two factors.